Effects of Caffeine Treatment for Apnea of Prematurity on Cortical Speech-Sound Differentiation in Preterm Infants. (March 2015) - Maitre, Nathalie L.; Chan, Jeremy; Stark, Ann R.; Lambert, Warren E.; Aschner, Judy L.; Key, Alexandra P.
Caffeine, standard treatment for apnea of prematurity, improves brainstem auditory processing. We hypothesized that caffeine also improves cortical differentiation of complex speech sounds. We used event-related potential methodology to measure responses to speech-sound contrasts in 45 intensive care neonates, stratified by cumulative exposure as no-, low-, and high-caffeine groups. Sound differentiation in the low-caffeine group and near-term no-caffeine infants was similar with repeated measures analysis of variance controlling for gestational and postnatal age. However, a generalized estimating equation approach demonstrated that, at equivalent postnatal age, differentiation was reduced in the high-caffeine (gestational age 25 weeks) compared to the low-caffeine group (gestational age 28 weeks), reflecting the importance of maturity at birth (Z = 2.77, P < .006). We conclude that caffeine improves measures of auditory processing associated with improved neurodevelopmental outcomes in preterm infants. However, current usage of caffeine for apnea of prematurity cannot fully compensate for the effects of brain immaturity on speech sound processing.